THE UTILIZATION OF DURIAN'S ALBEDO FLOUR AS SUBSTITUTION OF CORNSTARCH IN THE MAKING OF ICE CREAM (Universitas Negeri Semarang, 2018)
This research is to find out the process to make an ice cream using durian’s albedo flour. Start from to make durian albedo flour, to check content of durian’s albedo flour ice cream (pectin, protein, fat, and carbohydrate), to find out respondents’ opinion about display, color, smell, texture, and flavor of durian’s albedo ice cream, and also interests of respondents about ice cream using durian’s albedo flour. Populations of this research are spread at Wonorejo Permai Residence, Universitas Ciputra, and Bukit Darmo Boulevard. Researchers are choosing 30 random respondents as sample. There are few steps to collect the data. First, experiment method which had done three times for both of durian’s albedo flour and ice cream using durian’s albedo flour. Second, observation method, the researcher compared the result from experiments which had been done in the experiment method. Third, laboratory test, to find out the content of pectin, protein, fat, and carbohydrate from the ice cream using albedo durian flour. Fourth, organoleptic test to find out the shape, texture, flavor, and smell of ice cream using albedo durian flour. To do an organoleptic test, an ice cream will tested at laboratory, then distribute to the 30 random respondents and they will give their opinion in the questionnaires. Fifth is the descriptive statistics, where the researcher will process the questionnaire’s results. Based on the research that has been done, it concluded that durian’s albedo from the skin waste could be used as the ingredients for processed food. Moreover, based on organoleptic test with 30 respondents, shown that 96.7% of respondents interest with durian’s albedo ice cream.